Cotton Defoliation Evaluations, 1996 - Silvertooth, J. C. (College of Agriculture, University of Arizona (Tucson, AZ), 1997)
Two field experiments were conducted near Coolidge and Marana, AZ in 1996 to evaluate the effectiveness of a number of defoliation treatments on Upland (var. DPL 5415) and Pima (var. S-7) cotton.. All treatments consisted of materials commercially available in Arizona, and each showed promise in terms of overall effectiveness. Results do reinforce recommendations regarding the use of low rates (relative to the label ranges) under warm weather conditions and increasing rates as temperatures cool.